A new species of Elathous Reitter, 1890 (Coleoptera: Elateridae) from Lebanon. Issue 4 (2nd October 2021) - Németh, Tamás
Abstract : A new species of the genus Elathous Reitter, 1890 from Lebanon is described and illustrated. Elathous nemeri sp. nov. is similar to other Levantine species, but can be easily recognised from its congeners by its elongated pronotum as well as by the shape of the male genitalia. http://www.zoobank.org/urn:lsid:zoobank.org:pub:9A2D7DAF-7B6B-4BEF-8866-1000FCACC91F